(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The significance of determining specific pathomorphological changes and morphometric indices of lymphoid structures of the intestinal wall in children who died from acute intestinal infections in assessing the level and activity of the local intestinal immune system against acute infection depending on the age of children and premorbid diseases was studied.